2018
DOI: 10.1111/joa.12913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative multi‐scale hierarchical structure of the tail, plantaris, and Achilles tendons in the rat

Abstract: Rodent tendons are widely used to study human pathologies such as tendinopathy and repair, and to address fundamental physiological questions about development, growth, and remodeling. However, how the gross morphology and multi‐scale hierarchical structure of rat tendons, such as the tail, plantaris, and Achilles tendons, compare with that of human tendons are unknown. In addition, there remains disagreement about terminology and definitions. Specifically, the definitions of fascicle and fiber are often depen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 63 publications
1
37
0
Order By: Relevance
“…Tendinopathy, degeneration of the tendon that leads to pain and dysfunction, is common in both sports and occupational settings, but the mechanisms for tendinopathy are still unknown. The mechanisms of tendinopathy have been attributed to overloading that leads to inferior mechanical and microstructural degradation, and these occur across multiple hierarchical scales . Rodent tendon models of overloading have frequently been used to study tendinopathy; however, the multi‐scale mechanisms of normal load transfer and damage are not well understood.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Tendinopathy, degeneration of the tendon that leads to pain and dysfunction, is common in both sports and occupational settings, but the mechanisms for tendinopathy are still unknown. The mechanisms of tendinopathy have been attributed to overloading that leads to inferior mechanical and microstructural degradation, and these occur across multiple hierarchical scales . Rodent tendon models of overloading have frequently been used to study tendinopathy; however, the multi‐scale mechanisms of normal load transfer and damage are not well understood.…”
mentioning
confidence: 99%
“…Using the rat tail tendon, we recently showed that micro‐scale sliding is a mechanism for load transfer, and non‐recoverable micro‐scale sliding in response to high tensile loading leads to tendon damage . Yet, the rat tail tendon is specialized and is a relatively non‐load‐bearing tendon, and thus the load transfer and damage mechanisms are still unknown for load‐bearing rat tendons. Despite some differences between the rat tail tendon and load‐bearing tendons, we hypothesize that micro‐scale sliding is a mechanism for both tendons since they both have similar fiber structures .…”
mentioning
confidence: 99%
See 3 more Smart Citations